ANALISIS KEBUTUHAN DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE DI KOTA KENDARI (STUDI KASUS PADA MAHASISWA PASCASARJANA UNIVESITAS HALU OLEO) - Nursaadha Rajuddin, Wa Ode; Azis Muthalib, Dzulfikri (JIM : Journal Of International Management, 2022)
This study aims to determine and analyze: (1) The effect of needs and lifestyle simultaneously on smartphone purchasing decisions in Kendari City; (2) The influence of needs on smartphone purchasing decisions in Kendari City; (3) The influence of lifestyle on smartphone purchasing decisions in Kendari City. This research is a research with a descriptive quantitative approach, which is designed to obtain empirical evidence, test and analyze the needs and lifestyle of smartphone purchasing decisions in Kendari City. The population in this study were all smartphone users with a sample of 100 respondents. Sampling was carried out using purposive sampling technique. Collecting data in this study is to use a questionnaire. Data analysis techniques use two methods of analysis, namely descriptive and quantitative analysis. The results of this study are: (1) Needs and lifestyle simultaneously have a positive and significant effect on smartphone purchasing decisions; (2) Needs have a positive and significant effect on smartphone purchasing decisions; (3) Lifestyle has a positive and significant effect on smartphone purchasing decisions.